A farinha do cruzeiro: territorialidade sobre ameaças no Baixo Tocantins/PA - MORAES, Nívea Maria de (2024)
This work analyzed the relationship of the artisanal process of flour roasting, considering the relevant aspects for a good quality of the product, given the varieties of cassava and the production techniques employed. We also highlight the educational aspects that occur in the gardens and in the retreat, during the process of flour production, in the Caeté Cruzeiro community, municipality of Barcarena, in the state of Pará. As well as the various lexical forms created within these spaces of cultural knowledge and non-school learning. In this sense, the objective of the work is to ethnograph the production process of cassava flour in ceso de enseñanza, adethe community under study, its specific work languages, the dynamics of learning and its modes of production from planting to harvesting, going through the environment where it is grown until the roasting of the flour. Based on the concern of threats of the disappearance of such activity and artisanal techniques that contribute to food, such as paid activity in multinational companies installed in the region, power transmission lines, the sale of land to farmers. We used the qualitative method, with the help of the timestamp application, to map the manioc gardens, the flour houses (retreats). To obtain the data, interviews were conducted with farmers from the rural community and on-site observation.